Relationship between lower-limb muscle strength and functional independence among elderly people according to frailty criteria: a cross-sectional study - Batista, Fernanda Sotello; Gomes, Grace Angélica de Oliveira; D’Elboux, Maria José; Cintra, Fernanda Aparecida; Neri, Anita Liberalesso; Guariento, Maria Elena; Souza, Maria da Luz Rosário de (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Muscle strength and functional independence are considered to be determinants of frailty levels among elderly people. The aim here was to compare lower-limb muscle strength (LLMS) with functional independence in relation to sex, age and number of frailty criteria, and to ascertain the influence of these variables on elderly outpatients’ independence. DESIGN AND SETTING: Quantitative cross-sectional study, in a tertiary hospital. METHODS: The study was conducted on 150 elderly outpatients of both sexes who were in a cognitive condition allowing oral communication, between October 2005 and October 2007. The following instruments were used: five-times sit-to-stand test (FTSST), Functional Independence Measurement (FIM) and Lawton’s Instrumental Activities of Daily Living Scale (IADL). Descriptive, comparative, multivariate, univariate and Cronbach alpha analyses were performed. RESULTS: The mean time taken in the FTSST was 21.7 seconds; the mean score for FIM was 82.2 and for IADL was 21.2; 44.7% of the subjects presented 1-2 frailty criteria and 55.3% > 3 criteria. There was a significant association between LLMS and functional independence in relation to the number of frailty criteria, without homogeneity regarding sex and age. Functional independence showed significant influence from sex and LLMS. CONCLUSION: Elderly individuals with 1 or 2 frailty criteria presented greater independence in all FTSST scores. The subjects with higher LLMS presented better functional independence.